(untitled) (Global Journal of Management and Business Research, 2017)
The study examined the impact of capital budget expenditure implementation on economic growth in Nigeria. Specifically the study assessed the impact of implementation of capital expenditure on administration, economic services, socio-community services on the growth of Nigerian economy. Secondary data used in the study were collated from Central Bank of Nigeria(CBN) statistical bulletins, and analyzed with the use of Augmented Dickey-Fuller unit root test, co-integration test and error correction model (ECM) analysis. The long run normalized estimation reported coefficient values of -387, 2292, 69.05, 184.17 for capital expenditure on administration, economic services and socio-community services respectively, while the short run parsimonious ECM estimation reported coefficient estimates and probability value of 27.20(p=0.11), -27.82(p=0.001), -17.23(p=0.49) respectively. Thus, it was concluded that capital expenditure implementation is germane in maintaining and sustaining economic growth in Nigeria. Hence, it was recommended that government should ensure adequate implementation of capital expenditure in the country especially in areas of economic and socio-community services and also overhaul ministries, government agencies and parastatals to curb and curtailloopholes impeding effective and efficient implementation of capital budget in the country.